Sorption Analysis of 137Cs On Karawang’s Clay Samples - Budi Setiawan; Suci Prihastuti; Setyo S. Moersidik (Graduate Program of Syiah Kuala University, 2016)
The objective of this work is to characterize the specific of distribution coefficient (Kd) values of 137Cs onto Karawang’s clay for radioactive waste disposal facility purpose. Sorption phenomena was affected by contact time, ionic strength and loaded concentration of CsCl. Experiments were done in a batch method, with initial concentration was 10-8 M CsCl in the experiments of contact time and ionic strength effects. In the CsCl loading experiment, the concentration was varied from 10-8 to 10-4 M CsCl and 137Cs radioactive solution was used as a tracer. The solid-liquid ratio is 10-2 g/mL. The results shown that obtained Kd values were 21,714 and 4035 mL/g after contacted for 8 days for Sample-1 and 2, respectively. The presence of K+ and Na+ ions in solution had reduced the Kd value Cs-137 where the effect of K+ is greater than Na+ on decreased the value of Kd. The increasing of CsCl concentrations in solution had reduced the value of Kd. In both samples of clay were closely fit to Freundlich isotherm and pseudo-second order kinetic model. The results are very useful as the input of the safety assessment activity of site candidate for radioactive waste disposal facility in the future.